EVALUASI EFEKTIVITAS IMPLEMENTASI TOTAL QUALITY MANAGEMENT PADA GEORGETTE TEXTILES - Asrunputri, Aisyah Pia (JURISMA : Jurnal Riset Bisnis & Manajemen, 2019)
Total Quality Management (TQM) is a management philosophy that can help organization to reach its consistency on the effectiveness and efficiency of the production. The motivation in doing this research is due to the opportunity for excess of inventory, defect and over-processing to occur in the process of production despite the implementation of TQM. This research is meant to evaluate the effectiveness of TQM Implementation at Georgette Textiles. The author use in-depth interview to gather all the necessary information required on the effectiveness of the TQM Implementation. It can be concluded that Georgette Textiles have the effective implementation of TQM despite its issue on waste management that still can be tolerated. It is recommended for the management to use quality benchmarking to help the organization reach its business excellence and to eliminate quality gaps in the production.